PENGAJARAN BAHASA INDONESIA DALAM KURIKULUM BERBASIS KOMPETENSI - H. Akmal Hamsa (Universitas Pendidikan Ganesha, 2010)
In reformation era, people wish to have changes in various dimensions of life. They attempt to developthe quality of human resources in order to have high competitive power through the modificationof educational curriculum, which is in accordance with the change of time and the demandof community development.The operation of the educational system, therefore, has moved from centralized system to decentralizedone. This movement can be considered as the consequence of the application of the educationalrule No. 20, the year 2003. In this case, competency based curriculum implies that theteaching of language and Indonesian literature refers to the achievement of standard competencybased on the nature of the teaching and learning of indonesian, that is, communicative competenceand literature appreciation. These two competencies should be presented through the teaching andlearning of language (communicative) skills, and should be done integratedly, both in an attempt toachieve linguistic competency and to achieve competency in literary appreciation.Key words: teaching and learning, Indonesian language, competency based curriculum